Genotyping of Salmon Gill Poxvirus Reveals One Main Predominant Lineage in Europe, Featuring Fjord- and Fish Farm-Specific Sub-Lineages - Gulla, Snorre; Tengs, Torstein; Mohammad, Saima Nasrin; Gjessing, Mona; Garseth, Åse Helen; Sveinsson, Karoline; Moldal, Torfinn; Petersen, Petra E.; Tørud, Brit; Dale, Ole Bendik; Dahle, Maria K. (Frontiers in Microbiology, 2020)
Salmon gill poxvirus (SGPV) can cause serious gill disease in Atlantic salmon (Salmo salar L.) and represents a significant problem to aquaculture industries in Northern Europe. Here, a single-tube multi-locus variable-number tandem-repeat (VNTR) analysis (MLVA) genotyping assay, targeting eight VNTR loci, was developed for studying the epizootiology of SGPV. Through MLVA typing of SGPV positive samples from 180 farmed and wild Atlantic salmon in Northern Europe, the first molecular population study of this virus was undertaken. Comparison of resulting MLVA profiles by cluster analysis revealed considerable micro-diversity, while only a limited degree of specific clustering by country of origin could be observed, and no clustering relating to the severity of disease outbreaks. Phylogenetic analysis, based on genomic data from six SGPV specimens (three Norwegian, one Scottish, one Faroese and one Canadian), complemented and corroborated MLVA by pointing to a marked transatlantic divide in the species, with one main, relatively conserved, SGPV lineage as predominant in Europe. Within certain fjord systems and individual freshwater salmon smolt farms in Norway, however, discrete MLVA clustering patterns that prevailed over time were observed, likely reflecting local predominance of specific SGPV sub-lineages. MLVA typing was also used to refute two suspected instances of vertical SGPV transmission from salmon broodstock to offspring, and to confirm a failed disinfection attempt in one farm. These novel insights into the previously undocumented population structure of SGPV provide important clues e.g. regarding the mechanisms underlying spread and recurrence of the virus amongst wild and farmed salmon populations, but so far no indications of more or less virulent SGPV sub-lineages have been found. The MLVA scheme represents a highly sensitive genotyping tool particularly well suited for illuminating SGPV infection routes, and adds to the relatively low number of MLVA protocols that have so far been published for viral species. Typing is reasonably inexpensive, with a moderate technological requirement, and may be completed within a single working day. Resulting MLVA profiles can be readily shared and compared across laboratories, facilitating rapid placement of samples in an international ezpizootiological context.